2020
DOI: 10.3390/genes11090984
|View full text |Cite
|
Sign up to set email alerts
|

A 24-Week Physical Activity Intervention Increases Bone Mineral Content without Changes in Bone Markers in Youth with PWS

Abstract: Bone mineral density (BMD) is of concern in Prader-Willi syndrome (PWS). This study compared responses to a physical activity intervention in bone parameters and remodeling markers in youth with PWS (n = 45) and youth with non-syndromic obesity (NSO; n = 66). Measurements occurred at baseline (PRE) and after 24 weeks (POST) of a home-based active games intervention with strengthening and jumping exercises (intervention group = I) or after a no-intervention period (control group = C). Dual x-ray absorptiometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In these intervention studies, eight distinct PA interventions were assessed in one randomized controlled trial (RCT) [ 14 ], four non-randomized controlled trials [ 19 , 20 , 21 , 22 ] and three single-group intervention studies [ 8 , 23 , 24 ]. Six additional studies reported the effect of these eight interventions [ 13 , 15 , 16 , 25 , 26 , 27 ]. Among the five randomized or non-randomized controlled trials, two were rated as good-quality trials [ 14 , 21 ], two as a fair-quality trial [ 19 , 20 ], and two as poor-quality trials [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In these intervention studies, eight distinct PA interventions were assessed in one randomized controlled trial (RCT) [ 14 ], four non-randomized controlled trials [ 19 , 20 , 21 , 22 ] and three single-group intervention studies [ 8 , 23 , 24 ]. Six additional studies reported the effect of these eight interventions [ 13 , 15 , 16 , 25 , 26 , 27 ]. Among the five randomized or non-randomized controlled trials, two were rated as good-quality trials [ 14 , 21 ], two as a fair-quality trial [ 19 , 20 ], and two as poor-quality trials [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with the known effect of PA in adults with non-syndromic obesity, in whom only a weight loss of small magnitude (2 to 3 kg on average) is observed after an exercise training program [ 37 ]. In children with PWS, PA interventions seem to have a beneficial effect on lean body mass [ 20 , 22 , 26 ] and bone mineral density, which is an important major health benefit in these patients with low baseline values of lean body mass and bone mineral density [ 15 ]. Observational studies have also reported a positive relation between habitual PA and lean body mass [ 22 , 29 ] or bone parameters [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They propose that further longitudinal studies are needed to characterize the gut microbiota profile in PWS and its role. Rubin et al [ 13 ] then reported on a 24-week physical activity intervention program in PWS and found increases in bone mineral content without changes in bone markers in the youth with PWS via this intervention. They found that the youth with PWS had increased spine bone mineral content following physical activity interventions; however, bone remodeling markers remained unaltered.…”
mentioning
confidence: 99%